Health and medical informatics education: perspectives for the next decade - Haux, Reinhold (International journal of medical informatics, 1998)
It is argued that the progress of information processing and information technology changes our societies. Examples are given that there is a significant economic relevance of information technology for medicine and healthcare and for the quality of healthcare as well. In order to adequately pursue the goal of ‘Transforming healthcare through innovative use of information technology for the 21st century’ (the topic of the 6th International Conference on Health and Medical Informatics Education and of this special issue of the International Journal of Medical Informatics), health professionals are needed who are well-educated in health informatics or medical informatics, respectively. Raising the scope and the quality of education in the field of health and medical informatics would help to raise the quality and efficiency of healthcare. In this context the International Medical Informatics Association (IMIA) and its working group 1 (WG1) on Health and Medical Informatics Education can make a contribution by disseminating information and by elaborating recommendations on courses and programs in health and medical informatics. For this purpose IMIA WG1 has established a WWW site (http://www.imia.org/wg1) with information on health and medical informatics programs and courses. All teachers and institutions are encouraged to submit information about courses and programs offered and to set pointers to their own WWW sites. In addition, a mailing list was installed to facilitate communication between all persons involved in health and medical informatics education. For subscription, a message has to be sent to ‘listservrelay.urz.uni-heidelberg.de’. The body of the message should read ‘SUBSCRIBE IMIA-WG1’.
Gesehen am 05.08.2025